Social control, stoicism and slave ideology. The revolt of eunus in the work of Diodorus Siculus - Garcia Mac Gaw, Carlos (AADEC - UNL, 2016)
We discuss fragments of Diodorus Siculus where some mechanisms of domination of masters over slaves occurs. We note the representation of the social controland the will of concealment of the violent practices of slavery made from the dominant discourse. These fragments refer to specific situations that occurred both in domestic and productive spaces. The theory of social domination of O. Patterson and concepts of analysis of discourse are foundations on which our methodological approach is developed.